The Emerging Complexity of γδT17 Cells - McKenzie, Duncan R.; Comerford, Iain; Silva-Santos, Bruno; McColl, Shaun R. (Frontiers in Immunology, 2018)
Pre-programmed IL-17-producing γδ T cells constitute a poorly understood class of lymphocytes that express rearranged antigen receptors but appear to make little use of them. γδT17 cells were first characterized as tissue-resident sentinels with innate effector function. However, ongoing research continues to reveal unexpected complexity to this unusual subset, including phenotypic plasticity, memory-like activity and unique migratory behavior. Despite these advances, at the core of γδT17 cell biology remain fundamental gaps in knowledge: Are γδT17 cells truly innate or has the importance of the T cell receptor been overlooked? How unique are they among IL-17-producing lymphocytes? How similar are these cells between mice and humans? We speculate that answering these unresolved questions is key to successful manipulation of γδ T cells in clinical settings.